Journal of Globalization and Development (De Gruyter, 2010)
The Journal of Globalization and Development (JGD) publishes academic research and policy analysis on globalization, development and the complex interactions between them. It is dedicated to stimulating a dialogue between theoretical advances and rigorous empirical studies to push forward the frontiers of development analysis and seeks to combine academic insights with the in-depth knowledge of practitioners to address important policy issues.